Space, Place, and Gender - Massey, Doreen B. (University of Minnesota, 2007)
A leading feminist geographer puts forth new ways of thinking about space and place. In these days of global acceleration on the one hand and intensifying local nationalisms on the other, how should we be thinking about space and place? This new book brings together Doreen Massey's key writings on this debate. In it she argues that we have seen some problematical readings of both terms in recent years, and she proposes an alternative approach more adequate to the issues facing the social sciences today. Massey has organized these debates around the three themes of space, place, and gender. She traces the development of ideas about the social structure of space and place, and the relation of both to issues of gender and certain debates within feminism. Beginning with the economy and social structures of production, Massey develops a wider notion of spatiality as the product of intersecting social relations. On this basis she proposes an approach to "places" that is essentially open and hybrid while always provisional and contested. The themes intersect with much current thinking about identity within feminism and cultural studies. The chapters range from studies of the concepts of place employed in debates on uneven regional development and inner-city problems to arguments about the relationship between the conceptualization of space/place and the social construction of gender relations.